2021
DOI: 10.3390/pharmacy10010001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility and Cost Effectiveness of Long-Acting Lipoglycopeptides Used in Deep-Seated Infections among Patients with Social and Economic Barriers to Care

Abstract: The use of long-acting lipoglycopeptides (LaLGPs) in serious, deep-seated infections is of increasing interest. The purpose of this study is to evaluate the economic and clinical utility of LaLGPs in patients requiring protracted antibiotic courses who are not ideal candidates for oral transition or outpatient parenteral antibiotic therapy (OPAT). This is a retrospective, observational, matched cohort study of adult patients who received a LaLGP. Patients were matched 1:1 to those who received standard of care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…Moreover, the duration of hospitalization was 22.9 days in the LaLGP group compared to 32 days in the standard-of-care group [40]. Although LaLGP were associated with numerical, though not statistically significant, cost savings and reduced length of stay versus standard of care, the administration of LaLGP may be beneficial for patients with deep-seated, Gram-positive bacterial infections who have socioeconomic factors that preclude oral transition, or OPAT [40]. Finally, another study evaluating the impact of dalbavancin on both hospital length-of-stay and treatment-related costs in a cohort of patients with diverse Gram-positive bacterial infections reported that a median of EUR 8259 and 14 hospital days per patient who received dalbavancin therapy were saved.…”
Section: Pharmacoeconomic Characteristicsmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, the duration of hospitalization was 22.9 days in the LaLGP group compared to 32 days in the standard-of-care group [40]. Although LaLGP were associated with numerical, though not statistically significant, cost savings and reduced length of stay versus standard of care, the administration of LaLGP may be beneficial for patients with deep-seated, Gram-positive bacterial infections who have socioeconomic factors that preclude oral transition, or OPAT [40]. Finally, another study evaluating the impact of dalbavancin on both hospital length-of-stay and treatment-related costs in a cohort of patients with diverse Gram-positive bacterial infections reported that a median of EUR 8259 and 14 hospital days per patient who received dalbavancin therapy were saved.…”
Section: Pharmacoeconomic Characteristicsmentioning
confidence: 90%
“…Several studies have evaluated the cost-effectiveness of dalbavancin compared to other treatment options for various infections [39][40][41]. BJI correlates with a protracted hospital stay.…”
Section: Pharmacoeconomic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30] Additionally, multi-dose dalbavancin for complicated infections caused by Staphylococcus species and Streptococcus species is supported by more robust data, 28,31,32 some of which included matched cohorts and comparator groups. [33][34][35][36] As such, the OF may be most useful against complicated infections caused by Enterococcus species, particularly VRE. 18,37 Perhaps, the NF can replace the OF, though it is unclear how the NF and OF will coexist going forward.…”
Section: Dovepressmentioning
confidence: 99%